(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the environmental and agricultural impacts of limestone mining in Okpella, Edo State, Nigeria, using a survey research design. Data were collected from 400 respondents and analyzed using descriptive statistics, correlation, and regression techniques. The findings revealed that a majority of respondents perceived limestone mining as having severe environmental consequences, with 65% rating land degradation and 60% rating water contamination as extremely negative. Similarly, 52.5% of respondents reported extremely negative impacts on biodiversity, while 50% indicated severe vegetation loss. Regarding agricultural production, 55% of respondents strongly believed that mining has negatively affected soil quality, while 62.5% strongly believed that it has reduced crop yields. In addition, 50% strongly believed that mining disrupts agricultural practices. Descriptive statistics showed low mean scores (soil quality = 1.875; crop yield = 1.725), indicating strong agreement on the negative impacts. The correlation analysis revealed strong positive relationships among soil degradation, reduced crop yields, and disrupted farming practices (r = 0.694–0.782). Regression results indicated that limestone mining significantly affects crop production (R² = 0.612, p < 0.05), with a negative coefficient (B = -0.683), suggesting that increased mining intensity leads to declining agricultural output. The study concludes that limestone mining has significant adverse effects on environmental sustainability and agricultural productivity in Okpella. It recommends improved environmental management practices and further longitudinal and empirical research to support sustainable coexistence between mining and agriculture.